A revised ribosome–antibiotic model with proportional feedback synthesis explains recovery from translation inhibition - Brittany Howell; Matthew Scott (Journal of Theoretical Biology, 2026)

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Navigating danger: Watercraft-related mortality of sea turtles in the United States Atlantic and Gulf coastal waters - Mariana M.P.B. Fuentes; Brian A. Stacy; Susan G. Barco; Robert A. DiGiovanni; Karen M. Dourdeville; Kimberly F. Durham; Mark Faherty; Sarah A. Finn; Allen M. Foley; Matthew H. Godfrey; Robert F. Hardy; Lyndsey N. Howell; et al. (Biological Conservation, 2025)

Corrigendum to “Multiple-species resistance to avermectin/milbemycin anthelmintics on beef cattle farms in Georgia, USA” [Vet. Parasitol. 336 (2025) 110435] - Leonor Sicalo Gianechini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Multiple-species resistance to avermectin anthelmintics on beef cattle farms in Georgia, USA - Leonor Sicalo Gianchini; Kelsey L. Paras; Melissa M. George; Sue B. Howell; Bob Storey; Matthew J. Denwood; Ray M. Kaplan (Veterinary Parasitology, 2025)

Conservation aquaculture of wild-origin offspring preserves genetic diversity in an endangered population of white sturgeon - Peter Johnson; James Crossman; Andy Miller; Brent Nichols; Jason McLellan; Matthew Howell; Andrea Schreier (Conservation Genetics, 2025)
Conservation aquaculture programs that release fish to supplement wild populations can potentially capture greater genetic diversity by collecting offspring as embryos and larvae from wild spawning events than by producing them conventionally from broodstock. A conservation aquaculture program for the endangered white sturgeon population of the Upper Columbia River initially utilized wild broodstock for 14 years before fully transitioning to rearing wild-origin offspring in 2014. Here we evaluated the performance of this program in capturing the wild population’s genetic diversity since transitioning to wild-origin offspring. We analyzed genotypes of 325 tetrasomic single nucleotide polymorphism (SNP) markers in more than 5,000 offspring reared from 2014 to 2020 and over 1,000 wild adults from the population. Genetic diversity statistics were highly similar between each offspring year class and the wild adult population. We inferred sibship structure to estimate the total number of spawners (N s ) and effective number of breeders (N b ) represented within each year class and found values as high as 932.5 (95% CI 876–989) and 146.3 (95% CI 144–149), respectively, far surpassing the numbers included as broodstock. We further estimated N s and N b for three year classes with their individuals that died in aquaculture and found that on average, the mortality rate of 33.2% decreased N s by 21.5% and N b by 7.9%. Finally, we analyzed relationship coefficients to identify full-sibships spanning collection sites and found them in one year class, comprising 0.27% of all full-sibling pairs that year, demonstrating that the separate sites display negligible redundancy with respect to sibling families collected. Our results illustrate a robust performance by this program in representing the wild population’s diversity compared to broodstock approaches and support the adoption of utilizing wild-origin offspring in other conservation aquaculture programs when feasible.

Seismic hazard and shifting channels: Exploring coseismic river response - Erin McEwan; Timothy Stahl; Rob Langridge; Tim Davies; Andrew Howell; Matthew Wilson (Earth-Science Reviews, 2025)

Estimated golden eagle mortality from wind turbines in the western United States - Jay V. Gedir; Matthew J. Gould; Brian A. Millsap; Paige E. Howell; Guthrie S. Zimmerman; Emily R. Bjerre; Hillary M. White (Biological Conservation, 2025)

Development and application of a genetic baseline to inform bull trout (Salvelinus confluentus) passage and conservation in the Snake River - John S. Hargrove; Thomas A. Delomas; Matthew R. Campbell; Philip J. Howell; Audrey C. Harris; Richard Wilkison (Conservation Genetics, 2025)

Avian community responses to energy development and woody encroachment - John M. Yeiser; Paige E. Howell; Anna M. Matthews; Gregory T. Wann; Jim Giocomo; James A. Martin (Biological Conservation, 2024)

Transcriptomic analyses during development reveal mechanisms of integument structuring and color production - Adam M. M. Stuckert; Layla Freeborn; Kimberly A. Howell; Yusan Yang; Rasmus Nielsen; Corinne Richards-Zawacki; Matthew D. MacManes (Evolutionary Ecology, 2024)
Skin coloration and patterning play a key role in animal survival and reproduction. As a result, color phenotypes have generated intense research interest. In aposematic species, color phenotypes can be important in avoiding predation and in mate choice. However, we still know little about the underlying genetic mechanisms of color production, particularly outside of a few model organisms. Here we seek to understand the genetic mechanisms underlying the production of different colors and how these undergo shifting expression patterns throughout development. To answer this, we examine gene expression of two different color patches(yellow and green) in a developmental time series from young tadpoles through adults in the poison frog Oophaga pumilio. We identified six genes that were differentially expressed between color patches in every developmental stage ( casq1, hand2, myh8, prva, tbx3, and zic1). Of these, hand2, myh8, tbx3, and zic1 have either been identified or implicated as important in coloration in other taxa. Casq1 and prva buffer Ca 2+ and are a Ca 2+ transporter, respectively, and may play a role in preventing autotoxicity to pumiliotoxins, which inhibit Ca 2+ -ATPase activity. We identify further candidate genes (e.g., adh, aldh1a2, asip, lef1, mc1r, tyr, tyrp1, xdh ), and identify a suite of hub genes that likely play a key role in integumental reorganization during development (e.g., collagen type I–IV genes, lysyl oxidases) which may also affect coloration via structural organization of chromatophores that contribute to color and pattern. Overall, we identify the putative role of a suite of candidate genes in the production of different color types in a polytypic, aposematic species.

Wheat genetic resources have avoided disease pandemics, improved food security, and reduced environmental footprints: A review of historical impacts and future opportunities - Julie King; Susanne Dreisigacker; Matthew Reynolds; Anindya Bandyopadhyay; Hans‐Joachim Braun; Leonardo Crespo‐Herrera; Jose Crossa; Velu Govindan; Julio Huerta; Maria Itria Ibba; Carlos A. Robles‐Zazueta; Carolina Saint Pierre; et al. (Global Change Biology, 2024)
The use of plant genetic resources (PGR)—wild relatives, landraces, and isolated breeding gene pools—has had substantial impacts on wheat breeding for resistance to biotic and abiotic stresses, while increasing nutritional value, end‐use quality, and grain yield. In the Global South, post‐Green Revolution genetic yield gains are generally achieved with minimal additional inputs. As a result, production has increased, and millions of hectares of natural ecosystems have been spared. Without PGR‐derived disease resistance, fungicide use would have easily doubled, massively increasing selection pressure for fungicide resistance. It is estimated that in wheat, a billion liters of fungicide application have been avoided just since 2000. This review presents examples of successful use of PGR including the relentless battle against wheat rust epidemics/pandemics, defending against diseases that jump species barriers like blast, biofortification giving nutrient‐dense varieties and the use of novel genetic variation for improving polygenic traits like climate resilience. Crop breeding genepools urgently need to be diversified to increase yields across a range of environments (>200 Mha globally), under less predictable weather and biotic stress pressure, while increasing input use efficiency. Given that the ~0.8 m PGR in wheat collections worldwide are relatively untapped and massive impacts of the tiny fraction studied, larger scale screenings and introgression promise solutions to emerging challenges, facilitated by advanced phenomic and genomic tools. The first translocations in wheat to modify rhizosphere microbiome interaction (reducing biological nitrification, reducing greenhouse gases, and increasing nitrogen use efficiency) is a landmark proof of concept. Phenomics and next‐generation sequencing have already elucidated exotic haplotypes associated with biotic and complex abiotic traits now mainstreamed in breeding. Big data from decades of global yield trials can elucidate the benefits of PGR across environments. This kind of impact cannot be achieved without widescale sharing of germplasm and other breeding technologies through networks and public–private partnerships in a pre‐competitive space.

Transplant experiments demonstrate that larger brains are favoured in high‐competition environments in Trinidadian killifish - Kaitlyn J. Howell; Matthew R. Walsh (Ecology Letters, 2023)
The extent to which the evolution of a larger brain is adaptive remains controversial. Trinidadian killifish ( Anablepsoides hartii ) are found in sites that differ in predation intensity; fish that experience decreased predation and increased intraspecific competition exhibit larger brains. We evaluated the connection between brain size and fitness (survival and growth) when killifish are found in their native habitats and when fish are transplanted from sites with predators to high‐competition sites that lack predators. Selection for a larger brain was absent within locally adapted populations. Conversely, there was a strong positive relationship between brain size and growth in transplanted but not resident fish in high‐competition environments. We also observed significantly larger brain sizes in the transplanted fish that were recaptured at the end of the experiment versus those that were not. Our results provide experimental support that larger brains increase fitness and are favoured in high‐competition environments.

d ‐canavanine affects peptidoglycan structure, morphogenesis and fitness in Rhizobiales - Alena Aliashkevich; Matthew Howell; Pamela J. B. Brown; Felipe Cava (Environmental Microbiology, 2021)
Summary The bacterial cell wall is made of peptidoglycan (PG), a polymer that is essential for maintenance of cell shape and survival. Many bacteria alter their PG chemistry as a strategy to adapt their cell wall to external challenges. Therefore, identifying these environmental cues is important to better understand the interplay between microbes and their habitat. Here, we used the soil bacterium Pseudomonas putida to uncover cell wall modulators from plant extracts and found canavanine (CAN), a non‐proteinogenic amino acid. We demonstrated that cell wall chemical editing by CAN is licensed by P. putida BSAR, a broad‐spectrum racemase which catalyses production of dl ‐CAN from l ‐CAN, which is produced by many legumes. Importantly, d ‐CAN diffuses to the extracellular milieu thereby having a potential impact on other organisms inhabiting the same niche. Our results show that d ‐CAN alters dramatically the PG structure of Rhizobiales (e.g., Agrobacterium tumefaciens , Sinorhizobium meliloti ), impairing PG crosslinkage and cell division. Using A. tumefaciens , we demonstrated that the detrimental effect of d ‐CAN is suppressed by a single amino acid substitution in the cell division PG transpeptidase penicillin binding protein 3a. Collectively, this work highlights the role of amino acid racemization in cell wall chemical editing and fitness.

Combining Ecosystem and Single-Species Modeling to Provide Ecosystem-Based Fisheries Management Advice Within Current Management Systems - Daniel Howell; Amy M. Schueller; Jacob W. Bentley; Andre Buchheister; David Chagaris; Matthew Cieri; Katie Drew; Mathieu G. Lundy; Debbi Pedreschi; David G. Reid; Howard Townsend (Frontiers in Marine Science, 2021)
Although many countries have formally committed to Ecosystem-Based Fisheries Management (EBFM), actual progress toward these goals has been slow. This paper presents two independent case studies that have combined strategic advice from ecosystem modeling with the tactical advice of single-species assessment models to provide practical ecosystem-based management advice. With this approach, stock status, reference points, and initial target F are computed from a single-species model, then an ecosystem model rescales the target F according to ecosystem indicators without crossing pre-calculated single-species precautionary limits. Finally, the single-species model computes the quota advice from the rescaled target F , termed here F eco . Such a methodology incorporates both the detailed population reconstructions of the single-species model and the broader ecosystem perspective from ecosystem-based modeling, and fits into existing management schemes. The advocated method has arisen from independent work on EBFM in two international fisheries management systems: (1) Atlantic menhaden in the United States and (2) the multi species fisheries of the Irish Sea, in the Celtic Seas ecoregion. In the Atlantic menhaden example, the objective was to develop ecological reference points (ERPs) that account for the effect of menhaden harvest on predator populations and the tradeoffs associated with forage fish management. In the Irish Sea, the objective was to account for ecosystem variability when setting quotas for the individual target species. These two exercises were aimed at different management needs, but both arrived at a process of adjusting the target F used within the current single-species management. Although the approach has limitations, it represents a practical step toward EBFM, which can be adapted to a range of ecosystem objectives and applied within current management systems.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Population collapse dynamics in Acropora downingi , an Arabian/Persian Gulf ecosystem‐engineering coral, linked to rising temperature - Bernhard Riegl; Matthew Johnston; Sam Purkis; Emily Howells; John Burt; Sascha C. C. Steiner; Charles R. C. Sheppard; Andrew Bauman (Global Change Biology, 2018)
As in the tropical Atlantic, Acropora populations in the southern Persian/Arabian Gulf plummeted within two decades after having been ecosystem engineers on most wave‐exposed reefs since the Pleistocene. Since 1996/1998 live coral cover in the Gulf declined by over 90% in many areas, primarily due to bleaching and diseases caused by rising temperatures. In the formerly dominant table‐coral species A. downingi , population dynamics corresponding to disturbance regimes was quantified in three transition matrices (lower disturbance pre‐1996; moderate disturbance from 1998 to 2010 and 2013 to 2017, disturbed in 1996/1998, 2010/11/12, 2017). Increased disturbance frequency and severity caused progressive reduction in coral size, cover, and population fecundity. Small size‐classes were bolstered more by partial colony mortality than sexual recruitment. Some large corals had a size refuge and resisted die‐back but were also lost with increasing disturbance. Matrix and biophysical larval flow models suggested one metapopulation. Southern, Arabian, populations could be connected to northern, Iranian, populations but this connectivity was lost under assumptions of pelagic larval duration at rising temperatures shortened to a third. Then, the metapopulation disintegrated into isolated populations. Connectivity required to avoid extinctions increased exponentially with disturbance frequency and correlation of disturbances across the metapopulation. Populations became unsustainable at eight disturbances in 15 years, when even highest theoretical recruitment no longer compensated mortality. This lethal disturbance frequency was 3‐fold that of the moderately disturbed monitoring period and 4‐fold of the preceding low‐disturbance period—suggesting ongoing shortening of the disturbance‐free period. Observed population collapse and environmental changes in the Gulf suggest that A. downingi is heading toward at least functional extinction mainly due to increasingly frequent temperature‐induced mortality events, clearly linked to climate change.

(±)-MDMA and its enantiomers: potential therapeutic advantages of R(−)-MDMA - Elizabeth G. Pitts; Daniel W. Curry; Karly N. Hampshire; Matthew B. Young; Leonard L. Howell (Psychopharmacology, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Projecting Marine Mammal Distribution in a Changing Climate - Gregory K. Silber; Matthew D. Lettrich; Peter O. Thomas; Jason D. Baker; Mark Baumgartner; Elizabeth A. Becker; Peter Boveng; Dorothy M. Dick; Jerome Fiechter; Jaume Forcada; Karin A. Forney; Roger B. Griffis; et al. (Frontiers in Marine Science, 2017)

Inhibition of serotonin transporters disrupts the enhancement of fear memory extinction by 3,4-methylenedioxymethamphetamine (MDMA) - Matthew B. Young; Seth D. Norrholm; Lara M. Khoury; Tanja Jovanovic; Sheila A.M. Rauch; Collin M. Reiff; Boadie W. Dunlop; Barbara O. Rothbaum; Leonard L. Howell (Psychopharmacology, 2017)

Mapping a region within the 1RS.1BL translocation in common wheat affecting grain yield and canopy water status - Tyson Howell; Iago Hale; Ljupcho Jankuloski; Marcos Bonafede; Matthew Gilbert; Jorge Dubcovsky (Theoretical and Applied Genetics, 2014)

The Pel and Psl polysaccharides provide Pseudomonas aeruginosa structural redundancy within the biofilm matrix - Kelly M. Colvin; Yasuhiko Irie; Catherine S. Tart; Rodolfo Urbano; John C. Whitney; Cynthia Ryder; P. Lynne Howell; Daniel J. Wozniak; Matthew R. Parsek (Environmental Microbiology, 2012)
Summary Extracellular polysaccharides comprise a major component of the biofilm matrix. Many species that are adept at biofilm formation have the capacity to produce multiple types of polysaccharides. Pseudomonas aeruginosa produces at least three extracellular polysaccharides, alginate, Pel and Psl, that have been implicated in biofilm development. Non‐mucoid strains can use either Pel or Psl as the primary matrix structural polysaccharide. In this study, we evaluated a range of clinical and environmental P. aeruginosa isolates for their dependence on Pel and Psl for biofilm development. Mutational analysis demonstrates that Psl plays an important role in surface attachment for most isolates. However, there was significant strain‐to‐strain variability in the contribution of Pel and Psl to mature biofilm structure. This analysis led us to propose four classes of strains based upon their Pel and Psl functional and expression profiles. Our data also suggest that Pel and Psl can serve redundant functions as structural scaffolds in mature biofilms. We propose that redundancy could help preserve the capacity to produce a biofilm when exopolysaccharide genes are subjected to mutation. To test this, we used PAO1, a common lab strain that primarily utilizes Psl in the matrix. As expected, a psl mutant strain initially produced a poor biofilm. After extended cultivation, we demonstrate that this strain acquired mutations that upregulated expression of the Pel polysaccharide, demonstrating the utility of having a redundant scaffold exopolysaccharide. Collectively, our studies revealed both unique and redundant roles for two distinct biofilm exopolysaccharides.

Effects of exposure to amphetamine derivatives on passive avoidance performance and the central levels of monoamines and their metabolites in mice: Correlations between behavior and neurochemistry - Kevin Sean Murnane; Shane Alan Perrine; Brendan James Finton; Matthew Peter Galloway; Leonard Lee Howell; William Edward Fantegrossi (Psychopharmacology, 2012)

Panel of synaptic protein ELISAs for evaluating neurological phenotype - Paul E. Gottschall; Joanne M. Ajmo; Autumn K. Eakin; Matthew D. Howell; Hina Mehta; Lauren A. Bailey (Experimental Brain Research, 2010)

Behavioral and neurochemical effects of cocaine and diphenhydramine combinations in rhesus monkeys - Matthew L. Banks; Monica L. Andersen; Kevin S. Murnane; Rebecca C. Meyer; Leonard L. Howell (Psychopharmacology, 2009)

Interleukin-10 Polymorphisms, Cancer Susceptibility and Prognosis - W. Martin Howell; Matthew J. Rose-Zerilli (Familial Cancer, 2006)